Demographics of patients affected by surgical disease in rural hospitals in two sub-Saharan African countries: a retrospective analysis. (27th April 2015) - Grimes, Caris E; Billingsley, Michael L; Dare, Anna J; Day, Nigel; Mabey, Imogen; Naraghi, Sara; George, Peter M; Murowa, Michael; Kamara, Thaim B; Mkandawire, Nyengo C; Leather, Andy; Lavy, Christopher B D
Abstract: Background: Awareness is growing of both the importance of surgical disease as a major cause of death and disability in low-income and middle-income countries (LMICs) and the cost-effectiveness of fairly simple surgical interventions. We hypothesised that surgical disease predominantly affects young adults and is therefore significant in both the macroeconomic effect of untreated disease and the microeconomic effects on patients and families in low-resource settings. Methods: We retrospectively reviewed all admission data from two rural government district hospitals, Bo District Hospital in Sierra Leone and Thyolo District Hospital in Malawi. Both hospitals serve a rural population of roughly 600 000. We analysed data from 3 months in the wet season and 3 months in the dry season for each hospital by careful analysis of all hospital logbook data. For the purposes of this study, a surgical diagnosis was defined as a diagnosis in which the patient should be managed by a surgically trained provider. We analysed all surgical admissions with respect to patient demographics (age and sex), diagnoses, and the procedures undertaken. Findings: In Thyolo, 835 (12·9%) of 6481 hospital admissions were surgical admissions. In Bo, 427 (19·8%) of 2152 hospital admissions were surgical admissions. In Thyolo, if all patients who had undergone a procedure in theatre were admitted overnight, the total number of admissions would have been 6931, with 1344 (19·4%) hospital admissions being surgical and 1282 (18·5%) hospital patients requiring a surgical procedure. In Bo, 133 patients underwent a surgical procedure. This corresponded to 6·18% of all hospital admissions; although notably many of the obstetric admissions were referred to a nearby Médecins Sans Frontières (MSF) hospital for treatment. Analysis of the admission data showed that younger than 16-year-olds accounted for 10·5% of surgical admissions in Bo, and 17·9% of surgical admissions in Thyolo. 16–35-year-olds accounted for 57·3% of all surgical admissions in Bo and 53·5% of all surgical admissions in Thyolo. Men accounted for 53·7% of surgical admissions in Bo and 46·0% of surgical admissions in Thyolo. Analysis of the procedure data showed that younger than 16-year-olds accounted for 7·0% of procedures in Bo and 4·5% of procedures in Thyolo, with 16–35-year-olds accounting for 65·6% of all procedures in Bo and 84·4% of all procedures in Thyolo. Men underwent 63% of all surgical procedures in Bo, but only 7·7% of surgical procedures in Thyolo. This discrepancy is explained by the high rate of maternal surgery in Thyolo, which was not present in Bo because this service was provided at the nearby MSF hospital. Interpretation: Most people affected by disease requiring surgery are young adults. It would be expected that failure to provide surgical care could have long-term adverse effects on both individual and national wealth. Funding: The Sir Ratanji Dalal Scholarship from the Royal College of Surgeons of England.